Examination of characteristics and management of children with hearing loss and autism spectrum disorders. (September 2014) - Fitzpatrick, Elizabeth M.; Lambert, Linda; Whittingham, JoAnne; Leblanc, Emma
Abstract Objective: Up to 40% of children with hearing loss present with other developmental disabilities. The purpose of this study was to document the prevalence of autism spectrum disorders (ASD) in children with permanent hearing loss, to describe the audiologic characteristics, and to examine clinical management. Design: Prospective data related to clinical characteristics of children identified with hearing loss and ASD were examined. A retrospective chart review was also conducted to explore clinical management and uptake of amplification. Study sample: The study included all children in one Canadian region identified with permanent hearing loss and followed from 2002–2010. Results: Of a total of 785 children with permanent hearing loss, 2.2% (n = 17) also received a diagnosis of ASD. The 13 boys and 4 girls presented with a range of audiologic profiles from unilateral to profound bilateral hearing loss. Four of five children with unilateral hearing loss experienced progression to bilateral loss. Amplification was recommended for all but one child and 9 of 16 children continued to use their hearing devices. Conclusions: The higher prevalence rate of ASD in this clinical population is consistent with previous reports. Our findings suggest that some children with autism can derive benefits from the use of amplification.